Analisis Faktor Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Kendaraan Bermotor Di Kota Batam - Kristina Kristina; Viola Syukrina E Janrosl (eCo-Buss, 2022)
Tax is one of the sources of state revenue that is obligatory and used for state needs which is very important for the development of the Unitary State of the Republic of Indonesia and aims to improve mutual welfare. The Riau Islands Provincial Government has also felt the impact of the corona virus from the Regional Original Revenue sector or what is often called PAD, namely the decline in revenue from Motor Vehicle Tax Revenue. The sampling method in this study used a non-probability sampling method which was distributed to 100 respondents and the data analysis technique in this study used factor testing, data quality testing, classical assumption testing, multiple linear regression testing and hypothesis testing. By using SPSS version 25 program. The results of this study indicate that tax knowledge has a positive effect and tax quality, technology utilization, taxation taxes and taxpayer awareness have no positive effect on motor vehicle taxpayer compliance. Knowledge, tax service quality, technology utilization, mandatory tax sanctions, and taxpayer awareness simultaneously have a positive effect on taxpayer compliance in Batam City